2014
DOI: 10.1002/pssc.201300641
|View full text |Cite
|
Sign up to set email alerts
|

Swift Xe ion irradiation effect on structure and vibrational properties of undoped and Cd‐doped ZnO films

Abstract: The undoped and Cd‐doped (0.4, 0.5 at.%) ZnO films deposited by radiofrequency magnetron sputtering have been irradiated by 167 MeV Xe26+ ions with energy to a fluence 3×1012 ions/cm2. The structure and vibrational properties of as‐grown and irradiated samples were studied using X‐ray diffraction and Raman spectroscopy techniques. It was found that Cd‐doped ZnO films in comparison with undoped films demonstrate an improvement of crystal structure due to increased size of X‐ray coherent scattering regions, rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Presence of characteristic Raman modes such as E2 (low) at 100 cm -1 , E2 (high) at 438 cm -1 and even A1(TO) at 380 cm -1 of wurtzite ZnO structure indicates that major structural distortion has not been introduced due to irradiation (better viewed in right inset). Similar observation has also been reported by Myroniuk et al after swift Xe ion irradiation [65] on ZnO films. However, damage has indeed been introduced due to high energy O ions, though small, as seen from the ratio of intensities of 438 cm -1 and 582 cm -1 Raman modes, highest for ZnO-U (7.7) and lowest for ZnO-I (1.8).…”
supporting
confidence: 90%
“…Presence of characteristic Raman modes such as E2 (low) at 100 cm -1 , E2 (high) at 438 cm -1 and even A1(TO) at 380 cm -1 of wurtzite ZnO structure indicates that major structural distortion has not been introduced due to irradiation (better viewed in right inset). Similar observation has also been reported by Myroniuk et al after swift Xe ion irradiation [65] on ZnO films. However, damage has indeed been introduced due to high energy O ions, though small, as seen from the ratio of intensities of 438 cm -1 and 582 cm -1 Raman modes, highest for ZnO-U (7.7) and lowest for ZnO-I (1.8).…”
supporting
confidence: 90%
“…In this study we report the use of cathodoluminescence The doping by isoelectronic impurities can signicantly increase the chances of applications [5,6]. In particular, it was found that the small concentration of the cadmium (0.4 at.%) signicantly enhances the ultraviolet emission associated with excitonic transitions.…”
Section: Introductionmentioning
confidence: 95%
“…It can be explained by the (i) an increase in size of crystalline blocks, (ii) a relaxation of strain between grains in the lms and (iii) a reduction of defects in ZnO crystal lattice [6]. We suppose that cadmium can act as getter in zinc oxide, absorbing defects, which were generated during heavy ions irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Besides other attractive properties, ZnO is more resistant to radiation damage than other common semiconductors viz. Si, GaAs, GaN [39,40] and exhibits strong dynamic annealing effect i.e. even after bombardment with high energy ion irradiation it remains crystalline [41].…”
Section: Introductionmentioning
confidence: 99%